(untitled) (Medical Forum Monthly, 2020)
Objective: Enlist risk factors of thrombocytopenia in sick neonates and determine the outcome in sick neonates with thrombocytopenia in relation to risk factors. Study Design: Descriptive multi center case series study Place and Duration of Study: This study was conducted at the Pediatric Ward Teaching Hospital, D.G.Khan and Pediatric Unit-I, Nishtar Hospital, Multan from June 2019 to November 2019, Materials and Methods: A total of 100 sick neonates with thrombocytopenia were included in the study. Neonates with different risk factors like neonatal sepsis, birth asphyxia, prematurity,RDS, NEC and (jaundice, infant of diabetic mother) were evaluated and were included in the study Results: Among 100 cases with thrombocytopenia (platelets count< 150,000/ul) were included in this study. Out of 100 cases, 35(35%) were found to have early-onset thrombocytopenia and 65 cases (65%) were found to have late-onset thrombocytopenia. 23(67.4%) were with early-onset sepsis and 20 cases (46.5%) were late-onset sepsis. Out of 100 cases, 17(17%) cases were of birth asphyxia, 11 cases were of prematurity with gestational age <37 weeks and birth weight<2.5 kg, 6 cases of prematurity (54.5%) were with hemorrhagic skin manifestation and remaining were with occult mild thrombocytopenia. 20 cases of RDS with thrombocytopenia, 5 cases of NEC with thrombocytopenia and 4 cases with mild thrombocytopenia. The common manifestations in thrombocytopenic cases were petechiae and bruises followed by gastrointestinal hemorrhage. Conclusion: The leading causes of thrombocytopenia in sick neonates are sepsis, asphyxia, prematurity, RDS,NEC. Apart from the platelets counts the bleeding manifestations also depend upon underlying ailments.